Effect of Dam Body Conformations on Birth Traits of Calves in Chinese Holsteins - Jiayu Yang; Zhipeng Zhang; Xubin Lu; Zhangping Yang (Animals, 2023)
The objective of this study was to explore the effect of dam body conformations on birth traits including stillbirth, dystocia, gestation length and birth weight of Chinese Holstein calves and to provide a reference for improving cow reproductive performance. We collected phenotype data on 20 conformation traits of Chinese Holstein cows and analyzed the impact of dam conformation trait linear scores on stillbirth, dystocia, gestation length and calf birth weight. The feet angle, set of rear legs, fore udder attachment and rear attachment height traits of the dairy cows significantly affected the risk of stillbirth. The risk of dystocia decreases with the increase in stature and pin width. The bone quality of dairy cows had a significant positive correlation with gestation length. There was a significant positive correlation between fore udder attachment and calf weight at birth. The birth weight of calves from cows with high body conformation traits was significantly higher than that of calves with a low composite score. These results suggest that improving the body conformation traits, especially the selection of mammary system and body shape total score, will be beneficial in improving the reproductive performance of dairy cows.